LEARNING OPPORTUNITIES FOR ALL: THE INFORMATION TECHNOLOGY AS PANACEA - K., Tukur A. (Sokoto Educational Review, 2020)
Policy makers and educators make difficult choices among alternative educational improvement options. They emphasise increase in classroom size, school size etc. this paper, thus discussed learning opportunities available to formal education where information and communication technology has made sufficient learning opportunities for all categories. It also discussed the effects of Information Technology in learning vis-a-vis the teacher education providers in the country. It also proposed possible solutions to the problems o f employing IT in learning.